Experience-Based Learning Model to Increase Student Creativity - Lie, Catherine; Gonzales, Samantha; Martinez, Isabel (Al-Hijr: Journal of Adulearn World, 2024)
The growing emphasis on creativity in education has led to the exploration of various teaching methodologies that can enhance students’ creative thinking and problem-solving skills. Experience-based learning, which focuses on learning through real-world experiences, has been recognized as an effective model for fostering creativity. This approach emphasizes active engagement, reflection, and application of knowledge, allowing students to connect theory with practice. However, the impact of experience-based learning on student creativity remains underexplored. This study aims to investigate the effectiveness of the experience-based learning model in increasing student creativity, particularly in higher education contexts. A mixed-methods approach was employed, involving both qualitative and quantitative data collection methods. The study included 200 students from various disciplines who participated in experience-based learning activities. Data was collected through pre- and post-creativity assessments, student surveys, and interviews with educators. The results indicate that students who participated in experience-based learning activities showed a significant increase in creativity, particularly in areas such as problem-solving, idea generation, and innovative thinking. Students reported that hands-on experiences allowed them to approach challenges more creatively and with a deeper understanding of the subject matter. This study concludes that the experience-based learning model can significantly enhance student creativity, providing a more effective approach to fostering critical and creative thinking in education.